The scale-up of the surgical workforce. (27th April 2015) - Daniels, Kimberly M; Riesel, Johanna N; Meara, John G
Abstract: Background: Countries with fewer than 20 specialist surgeons, anaesthetists, and obstetricians (SAO) per 100 000 population have worse health outcomes. To achieve surgical workforce densities of 20 per 100 000 by 2030, a scale up of the surgical workforce is required. No previous study has shown what this will cost, how many providers will be required, or how long it will take to increase the global surgical workforce. We aim to identify these answers for health-care systems that employ SAO alone and for those that use a hybrid model of SAO and task shifting to inform strategic planning. Methods: Data for the density of SAO per country were obtained from the WHO Global Surgical Workforce Database. To find the total number of SAO that need to enter the workforce by 2030 to achieve surgical workforce thresholds of 20 per 100 000, the population growth formula (P= 0 e rt ) was used and we assumed exponential surgical workforce growth and two potential retirement rates of either 1% or 10%. We did not account for migration. The same calculations were used for associate clinicians needed to enter the workforce in either a 2:1 or 4:1 associate clinicians-to-SAO ratio. The costs to train SAO and associate clinicians were estimated with data for training costs imputed into a regression analysis with health-care expenditure per capita for each country. We assumed training costs will remain constant, and we did not account for inflation. The time needed to train new surgical and anaesthetic providers was estimated with average length of training for SAO and associate clinicians and was measured in person years. Two models (one for a system of SAO only and one for a hybrid of SAO and associate clinicians) were created to show how many providers will need to enter the workforce per year once training is complete to reach targets by 2030. The model did not involve the scale-up of the surgical workforce needed to address unmet needs of essential surgical services. Findings: By 2030, the world will need 1 272 586 new surgical workforce providers to meet a surgical workforce density of 20 per 100 000 assuming a 1% retirement rate. This will cost US71–146 billion depending on the model used. Low-income and lower-middle-income countries show the largest required scale-up. An additional 806 352 (median 3412 [IQR 691–6851]) providers are needed in those countries. In the SAO only model, this will cost a median of US19·66 per 2013 capita (IQR 15·79–25·07) and will take a median of 34 121 person years (IQR 6911–68 509). In the 4:1 associate clinician-to-SAO ratio, it will cost a median of US7·57 per capita and take 20 472 person years. When accounting for the delay of entry to the workforce due to training in these countries, the median rate of entry to meet the goal density will have to increase 10·9 times after a 10 year delay in an SAO only model as opposed to 4·98 times with a 5 year delay in the hybrid 4:1 associate clinician-to-SAO model. Interpretation: Although low-income countries, lower-middle-income countries, and upper-middle-income countries will require a surgical workforce scale-up, lower-middle-income countries will require the largest scale-up. In these countries, implementing a system of task shifting can decrease costs and training times by 40%. Meeting densities of 20 per 100 000 will not guarantee quality care or improved access in rural areas, and equal attention must be paid to the provision of safe, affordable, accessible surgical care to all who need it. Funding: None.